Design and implementation of a mobile app for public transportation services of persons with visual impairment (TransmiGuia) (2020)
Even though there exist lot of inclusive aids on the market, a joint research between Universidad El Bosque and Universidad de San Buenaventura have shown that visually impaired people still face several problems while attempting to access into the public transport system. Thus, with the insight gathered during this research, the Acoustic Research Group - University of San Buenaventura has designed an android mobile application called TransmiGuía. It works with geolocation, voice recognition and help visually impaired people to navigate through the public transport system.